2008
DOI: 10.1063/1.3006004
|View full text |Cite
|
Sign up to set email alerts
|

First-principles-based investigation of kinetic mechanism of SiC(0001) dry oxidation including defect generation and passivation

Abstract: Effect of gate oxidation method on electrical properties of metal-oxide-semiconductor field-effect transistors fabricated on 4H-SiC C (0001) face Appl.The key stages of the dry oxidation of the SiC͑0001͒ surface are analyzed based on first-principles calculations. It is found that an abrupt SiC/ SiO 2 interface model results in a large activation barrier of oxygen penetration to the silicon carbide, and thus the penetration is probably the rate-limiting step for the entire dry-oxidation process. The subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 58 publications
6
50
0
Order By: Relevance
“…Furthermore, an explanation of why the more diffusive O 2 does not contribute to the oxidation of Si-face SiC is needed. Gavrikov et al reported a barrier of 3.5 eV for O 2 diffusing through the last layer of SiO 2 on Si-face SiC, [22] which could have suggested that O 2 cannot be incorporated. However, they reported an even higher barrier of 4.5 eV for O i and concluded that O i is irrelevant for Si-face oxidation.…”
mentioning
confidence: 99%
“…Furthermore, an explanation of why the more diffusive O 2 does not contribute to the oxidation of Si-face SiC is needed. Gavrikov et al reported a barrier of 3.5 eV for O 2 diffusing through the last layer of SiO 2 on Si-face SiC, [22] which could have suggested that O 2 cannot be incorporated. However, they reported an even higher barrier of 4.5 eV for O i and concluded that O i is irrelevant for Si-face oxidation.…”
mentioning
confidence: 99%
“…Such defective structures have not yet been considered in the previous theoretical studies. 20,21,24,27,30 Apart from that, our non-abrupt interface model also include excited configurations, such as fivefold-coordinated Si atoms (SiO 5 ) and threefold-coordinated O atoms. The SiO 5 center does not mean the O enrichment of the interface because a fivefold-coordinated silicon event is accompanied by the generation of threefold-coordinated oxygen atoms.…”
Section: A Composition Of the Interfacial Transition Layermentioning
confidence: 99%
“…20,21 Gavrikov et al subsequently presented a kinetic mechanism of dry SiC oxidation based on the first-principles investigation. 24 They suggested that the carbon dimer generated during SiC oxidation probably is responsible for the NITs. However, these defects could not fully account for the TDRC and PST measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] It has been reported that C injection into the SiO 2 layer can be attributed to the interface state over a wide energy range, 20 and the injected C interstitials create C dimers/di-interstitials in the SiC layer, which gives rise to the interface state near the conduction band edge. 21,22 Furthermore, it has been assumed in the development of bipolar devices that C vacancies, which give rise to deep-level states called Z 1/2 centers, are filled with C interstitials that diffuse into the SiC layer during oxidation. [17][18][19] It is believed that such atomic emissions during oxidation can help explain device-killing defects.…”
mentioning
confidence: 99%